2021
DOI: 10.3389/fpsyg.2021.622462
|View full text |Cite
|
Sign up to set email alerts
|

Local Processing Bias Impacts Implicit and Explicit Memory in Autism

Abstract: Autism spectrum disorder (ASD) is characterized by atypical perception, including processing that is biased toward local details rather than global configurations. This bias may impact on memory. The present study examined the effect of this perception on both implicit (Experiment 1) and explicit (Experiment 2) memory in conditions that promote either local or global processing. The first experiment consisted of an object identification priming task using two distinct encoding conditions: one favoring local pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Experimenters found that autistic participants exhibited enhanced local processing of dynamic stimuli when presented over a longer time. A recent study (Lebreton et al., 2021) has also demonstrated local processing bias in autistic individuals using tasks that target local and global processing ability, with authors presenting potential links between this bias and impairments in memory. Overall, these results suggest that there is an imbalance in global/local visual processing that can impact the efficient processing of elements in the environment.…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimenters found that autistic participants exhibited enhanced local processing of dynamic stimuli when presented over a longer time. A recent study (Lebreton et al., 2021) has also demonstrated local processing bias in autistic individuals using tasks that target local and global processing ability, with authors presenting potential links between this bias and impairments in memory. Overall, these results suggest that there is an imbalance in global/local visual processing that can impact the efficient processing of elements in the environment.…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…Given that there has been evidence of reduced global processing in ASD, there is also evidence to suggest enhanced local processing of the visual field (Chen et al, 2012;Iarocci et al, 2006;Lebreton et al, 2021;Manning et al, 2015). Studies that test this deficit include those that utilize moving stimuli to evaluate motion coherence.…”
Section: Perceptual Deficitsmentioning
confidence: 99%
See 1 more Smart Citation